Pemikiran Pendidikan Islam KH. Hasyim Asy’ari (Perspektif Epistimologi Sosial Keagamaan Dan Konsep Pendidikan Islam Bagi Guru Dan Peserta Didik) - Martono Martono (Al-Fikr: Jurnal Pendidikan Islam, 2020)
Kyai Hasyim is known as a figure who is hungry for religious knowledge (Islam). To treat his thirst, KyaiHasyim traveled various famous places in Java at that time. Not only that, the cleric Hasyim also spent a longtime to explore Islam in the holy land (Mecca and Medina). It can be given, Kyai Hasyim is among the santriwho are really serious about Javanese philosophy, “luru ilmu kanti lelaku” (seeking knowledge bywandering) or wandering students.